Summation Processes and Gaussian Quadratures - Milovanović, Gradimir V. (Sarajevo Journal of Mathematics, 2024)
In this survey paper we present two classes of summation procedures based on ideas related to Gaussian quadratures. Such summation/integration procedures can be applied to the summation of slowly convergent series. Numerical examples are included. 2000 Mathematics Subject Classification. Primary 40A25; Secondary 30E20, 33C90, 65D32, 33F05